Multi Source Handphone Charging System For Communication During Emergencies - Azuka, Affam (2017)

(untitled)
Emergency situations may arise due to natural disaster occurrences or when chance takes one to a remote location. In settings like this, communication requires that mobile devices are powered on in the expectation of access to relief and rescue services. However, in many cases the electricity supply will be broke down. Usually, alternative energy sources provide the needed power to mobile phones in such circumstances. These alternative energy sources exhibit peculiar limitations that affect availability. This work was aimed at merging various alternative sources into a unit that will provide potential to a mobile phone with an emphasis on enhancing the efficiency of a hand-cranked electric dynamo source. Three power sources are employed which are active human power in the electric dynamo, solar panels and a pair of rechargeable batteries. Preliminary tests and analysis were conducted for hardware selection and assembly. The completed system contains a manual switch for the energy sources, a dc-dc regulation, battery charging electronic layout and a torchlight for illumination. An improved efficiency of 87.5% was achieved for the dynamo with the system able to deliver an average 0.4 W during operation. An average of 21 minutes elapsed before a minimum charge was delivered to a basic phone. The charging times for a smartphone to a determined level was found to be 108 minutes, 86 minutes and 72 minutes for the solar source, dynamo source and battery source, respectively. The developed unit is useful to people to keep it as a tool that they can rely on to power up their mobile phone in order to send emergency rescue message.